STUDI KARAKTERISTIK KARKAS BABI BALI ASLI DAN BABI LANDRACE YANG DIGUNAKAN SEBAGAI BAHAN BAKU BABI GULING - N. L. P., SRIYANI; ARIANA, I N.T. (Majalah Ilmiah Peternakan; Vol 21 No 2 (2018): Vol 21, No 2 (2018)DO - 10.24843/MIP.2018.v21.i02.p03, 2018)
This study aims to determine the differences of carcass characteristics of the two different breeds, such as bali pig and landrace pig. These domesticated animals used as raw material for suckling pig. A complete randomized design (CRD) was used with two different pigs, bali pig with traditional maintenance management and landrace pig with intensive maintenance management. Both species were used as samples between 2-3 months. They are tested using T Test (Two Independent Tests). The research was conducted at traditional slaughter housing for the needs of suckling pig. It showed that 16.17 kg weight of bali pig used for suckling pig which is significantly lower (P<0.05) than 35.06 kg of landrace pigs. The carcass weight of bali pig is 10.77 kg significantly lower (P<0.05) than 25.65 kg of landrace pig. The percentage of bali pig carcass is 66.98% significantly lower (P<0.05) than 73.12% landrace pigs. The value of fleshing index of bali pig carcass is 0.22 significantly lower (P<0.05) than 0.38 landrace pigs. Back fat thickness of bali pigs is 11.2 mm significantly higher (P<0.05) than 8.1 mm landrace pigs. It can be concluded that the quality of bali pig carcass is lower better compared to landrace pig carcass.